A Dyad Model of Peer-Assisted Learning in an Occupational Therapy Student Experiential Learning Clinic for Hand Therapy - De'lamor Aguilar; Vicki K. Kaskutas; Rose McAndrew (Journal of Occupational Therapy Education, 2023)
Peer-assisted learning (PAL) in healthcare education encourages critical thinking, professional development, knowledge acquisition, and enhancement of clinical skills. In this paper, we describe the pilot of a dyad model of PAL used in an occupational therapy (OT) student experiential learning clinic for hand therapy, where two students at the same knowledge level provided peer support to one another in clinical responsibilities. Example activities where dyad learning occurred include evaluation and treatment planning, care delivery, documentation, presenting during clinic rounds, practicing administering assessments and treatment techniques, and role-playing sensitive patient conversations. We developed two supplemental tools to support feedback between peers: the Session Rating Tool for post-treatment feedback and the Documentation Checklists for evaluating documentation. We assessed the effectiveness of the dyad model and the two tools by first exploring students’ anticipated impact on a total of nine criteria essential to professional growth and hand therapy clinical practice, which was rated on a Likert Scale. After a six-week pilot period, the same questions investigated students’ perception of actual impact. Students also provided qualitative feedback via open text on each survey. Students rated the dyad learning model highest for overall confidence in clinical skills/treating patients and rated the model’s impact higher than anticipated on clinical reasoning skills, therapeutic use of self and other communication skills, upper extremity diagnoses and conditions, and OT process. Students rated the Session Rating Tool similarly to anticipated impact. The dyad model of PAL supported student learning and clinical performance in this student experiential learning clinic.